The family gap in wages: what Wombmates reveal - Marianne Simonsen; Lars Skipper (Institute for the Study of Labor (IZA), 2009)
We shed new light on the effects of having children on hourly wages by exploiting access to data on the entire population of employed same-sex twins in Denmark. Our second contribution is the use of administrative data on absenteeism; the amount of hours off due to holidays and sickness. Our results suggest that childbearing reduces female hourly wages but the principal explanation is in fact mothers' higher levels of absence. We find a positive wage premium for fathers.
Keywords: J13; J24; J31; J71; 330; Fertility; wages; twins; Frauenerwerbstätigkeit; Fruchtbarkeit; Frauenarbeitslohn; Fehlzeit; Dänemark